HUBUNGAN ANTARA PENGETAHUAN DAN PERILAKU REMAJA PUTERI DALAM MENJAGA KEBERSIHAN ALAT GENITALIA DENGAN KEJADIAN KEPUTIHAN DI SMA NEGERI 2 PINELENG - Nanlessy, Deissy Marcelien; Hutagaol, Esther; Wongkar, Djon (JURNAL KEPERAWATAN)
Abstract: Flour Albus is more discharge from the vagina is sometimes itchy, pain, burning sensation in the genitl lips, often accompanied by foul odor, and cause pain during urination. The purpose of this study was to determine the relationship between knowledge an behavior of young girl in maintaining cleanliness of the genital apparatus with flour albus event in high school 2 pineleng. Method. This type of research uses observational analytic cross sectional design technigue that uses total side, responden was 60 with the inclusion and exclusion criteria. Results are presented in the from of frequency distribution table and analyzed using the Chi-square test with a significance level (a=0,05), data collection was done by using koesioner. Conclusion There is no relationship between knowledge young women in maintaining the cleanliness of the genital apparatus with with flour albusevents as many as 18 young girls with values p=0,628, and there is no relationship between behavior young women in maintaining the cleanliness of the genital apparatus with flour albus event as many as 21 young girl with values p=0,158. Keywords: Knowledge, Behavior, Flour Albus. Abstrak: Keputihan adalah keluarnya cairan berlebihan dari vagina yang terkadang disertai rasa gatal, nyeri, rasa panas dibibir kemaluan, kerap disertai bau busuk, dan menimbulkan rasa nyeri sewaktu buang air kecil. Tujuan. penelitian ini adalah untuk mengetahui hubungan antara pengetahuan dan perilaku remaja putri dalam menjaga kebersihan alat genitalia dengan kejadian keputihan di SMA Negeri 2 Pineleng. Metode. Jenis penelitian ini menggunakan observasional analitik dengan rancangan cross sectional yang menggunakan teknik total sampling, responden berjumlah 60 orang dengan criteria inklusi dan eksklusi. Hasil yang disajikan dalam bentuk tabel distribusi frekuensi dan dianalisis menggunakan Chi-square test dengan taraf signifikan (a=0.05). Pengambilan data dilakukan dengan menggunakan kuesioner. Kesimpulan dalam penelitian ini didapatkan tidak ada hubungan antara pengetahuan remaja putri dalam menjaga kebersihan alat genitalia dengan kejadian keputihan sebanyak 18 remaja putri dengan nilai p=0,628, dan tidak ada hubungan antara perilaku remaja putri dalam menjaga kebersihan alat genitalia dengan kejadian keputihan sebanyak 21 remaja putri dengan nilai p=0,158. Kata kunci: Pengetahuan, Perilaku, Kejadian keputihan